Validation of radiological reduction criteria with intraoperative cone beam CT in unstable syndesmotic injuries - Vetter, Sven Y.; Euler, Jeannie Jessica; Beisemann, Nils; Swartman, Benedict; Keil, Holger; Grützner, Paul Alfred; Franke, Jochen (European journal of trauma and emergency surgery, 2021)
Acute unstable syndesmotic lesions are regularly treated with closed or open reduction and fixation with either a positioning screw or tight rope. Conventional fluoroscopy is limited to identify a malreduction of the ankle mortise. The aim of the study was to validate the reduction criteria of intraoperative cone beam CT in unstable syndesmotic injuries by analyzing the clinical outcome.